ANALYSIS OF THE INFLUENCE OF VARIOUS MEANS OF GENERAL PHYSICAL TRAINING ON THE INDICATORS OF INTRACARDIAC HEMODYNAMICS AND DIASTOLIC HEART FUNCTION IN ATHLETES OF SENIOR RANKS IN BOXING - Neupokoev S.N.; Shilko V.G.; Bredikhina Yu.P.; Katkov V.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the effect of various means of general physical training on the indices of intracardiac hemodynamics and diastolic function of the heart in senior athletes in boxing. Methods and structure of the study. Two equivalent groups of boxers of the 1st category were formed, 10 people in each group: the experimental group (EG) and the control group (CG). The indicators of intracardiac hemodynamics and diastolic function of the heart were studied using various means of general physical training of senior athletes. Results and conclusions. It is noted that the use of general physical training means, involving the muscles of the lower extremities, contributes to the maximum and adequate activity of the cardiovascular system, which is qualitatively reflected in the indicators of the general physical training of senior athletes.